2001
DOI: 10.1161/hyp.38.4.896
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of eNOS in the RVLM Causes Hypotension and Bradycardia Via GABA Release

Abstract: In this study, we examine the role of NO located in the rostral ventrolateral medulla (RVLM) in the control of blood pressure and the activity of the sympathetic nervous system. To determine the effect of an increase in NO production in the RVLM on blood pressure in conscious rats, adenovirus vectors encoding either endothelial NO synthase (AdeNOS) or β-galactosidase (Adβgal) were transfected into the bilateral RVLM. The local expression of endothelial NO synthase (eNOS) protein in the RVLM was confirmed by im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(83 citation statements)
references
References 25 publications
5
74
0
4
Order By: Relevance
“…Similar changes in metric values were noted for the distribution of NO-neurons in rats with elevated blood pressure [1]. The changes observed in the medulla oblongata of experimental rats seem to be determined by the hypertensive effect of L-NAME [12]. It is well known that suppression of nitroxidergic mechanisms activates the sympathetic nervous system and increases blood pressure, while activation of nitroxidergic processes produces an opposite effect [10,12,13].…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Similar changes in metric values were noted for the distribution of NO-neurons in rats with elevated blood pressure [1]. The changes observed in the medulla oblongata of experimental rats seem to be determined by the hypertensive effect of L-NAME [12]. It is well known that suppression of nitroxidergic mechanisms activates the sympathetic nervous system and increases blood pressure, while activation of nitroxidergic processes produces an opposite effect [10,12,13].…”
Section: Resultssupporting
confidence: 57%
“…The changes observed in the medulla oblongata of experimental rats seem to be determined by the hypertensive effect of L-NAME [12]. It is well known that suppression of nitroxidergic mechanisms activates the sympathetic nervous system and increases blood pressure, while activation of nitroxidergic processes produces an opposite effect [10,12,13]. With increasing the time from the last L-NAME injection, blood pressure gradually returned to normal (over 3-4 weeks) and the differences between the control and experimental groups in most studied metric parameters decreased in all nuclei (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…In the NTS, the Ang II-induced facilitation of GABA release appears to be mediated by nitric oxide produced via endothelial nitric oxide synthase [39], and so this mechanism could also operate within the RVLM. Indeed, it has been demonstrated that overproduction of endothelial nitric oxide synthase in the RVLM causes a decrease in SNA, via increased release of GABA [40]. As shown in Figure 1, the AT1 receptors that trigger the release of nitric oxide may be located on the endothelial cells of blood vessels.…”
Section: Balance Between Tonic Excitatory and Inhibitory Inputs: Possmentioning
confidence: 97%
“…In animal models of hypertension icv infusion of an NADPH oxidase inhibitor or tempol, a SOD (superoxide dismutase) mimetic given to reduce central ROS production, decreases both RSNA (renal sympathetic nerve activity) and BP (blood pressure) [24,34,46]. Reductions in RSNA with icv tempol involve NO-mediated release of GABA within the RVLM [34,47]. Conversely, reducing NO by icv NOS inhibition using L-NMMA (N G -monomethyl-Larginine) increases sympathetic outflow [34].…”
Section: Experimental Backgroundmentioning
confidence: 99%